Pengaruh Budaya Positif dan Kompetensi Pedagogik Terhadap Kualitas Pembelajaran Guru SD Negeri Se-Kecamatan Todanan Kabupaten Blora - Emi Lutfia; Soedjono Soedjono; Harto Nuroso (Jayapangus Press, 2026)
The quality of learning of public elementary school teachers in Todanan District is still not optimal. In addition, a positive culture in schools has not been formed optimally. From the aspect of pedagogical competence, elementary school teachers in Todanan District are generally in the fairly good category, but not optimal. This study aims to test and analyze the influence of Positive Culture and Pedagogical Competence partially and simultaneously on the Quality of Teacher Learning. This study is a quantitative study with a population of 308 people, a sample of 174 people. The instrument tests used are validity and reliability tests. The classical assumption test uses a normality test, linearity test, multicollinearity test, and heteroscedasticity test. Data analysis uses multiple linear regression tests, F tests (ANOVA) and t tests. Based on the results of the study, it can be concluded as follows: (1) Positive Culture has a positive and significant effect on the Quality of Teacher Learning, based on the results of the calculated t test 8.462> t table 1.974 and a significance level of 0.000 <0.05; (2) Pedagogical Competence has a positive and significant effect on the Quality of Teacher Learning, based on the results of the t-test of 7.890 > t-table 1.974; (3) The influence of Positive Culture and Pedagogical Competence simultaneously has a positive and significant effect on the Quality of Teacher Learning, based on the results of the F-test of 7.890 > F-table (69.538 > 3.05). Simultaneously, the variables of Positive Culture (X1) and Teacher Pedagogical Competence (X2) simultaneously have a positive effect on the Quality of Learning variable (Y) with a multiple linear regression equation Ŷ = 18.032 + 0.217 X1 + 0.444 X2. The calculation results show a determination coefficient of R Square of 0.546, which means that variables (X1) and (X2) have a simultaneous effect of 44.9% on variable (Y).